2019
DOI: 10.1093/biolre/ioz002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macrophage depletion on characteristics of cervix remodeling and pregnancy in CD11b-dtr mice

Abstract: To test the hypothesis that macrophages are essential for remodeling the cervix in preparation for birth, pregnant homozygous CD11b-dtr mice were injected with diphtheria toxin (DT) on days 14 and 16 postbreeding. On day 15 postbreeding, macrophages (F4/80+) were depleted in cervix and kidney, but not in liver, ovary, or other non-reproductive tissues in DT—compared to saline—treated dtr mice or wild-type controls given DT or saline. Within 24 h of DT-treatment, the density of cell nuclei and macrophages decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…Our findings build on prior studies implicating homeostatic macrophages in fetal tolerance during early pregnancy (35,36,38,62) and midgestation (34,63) and expand on a report that systemic macrophage depletion from mice on 15 dpc caused fetal morbidity and mortality (28). However, earlier studies have not reported preterm birth or perinatal loss after macrophage depletion, suggesting the physiological roles of uterine macrophages depend on the gestational stage.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings build on prior studies implicating homeostatic macrophages in fetal tolerance during early pregnancy (35,36,38,62) and midgestation (34,63) and expand on a report that systemic macrophage depletion from mice on 15 dpc caused fetal morbidity and mortality (28). However, earlier studies have not reported preterm birth or perinatal loss after macrophage depletion, suggesting the physiological roles of uterine macrophages depend on the gestational stage.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, a recent study used a conditional knockout mouse model to deplete CD11b + F4/80 + macrophages throughout various subregions early in the ripening phase. As the first study to histologically confirm macrophage depletion during the transition from the soft to ripening phase of pregnancy, evidence supported a role for this immune cell in remodeling (34). The lack of collagen cross-linked degradation coupled with reduced cell nuclei density in the stroma when macrophages were depleted suggested ripening was blocked, but inflammation was ongoing due to extracellular space expansion or hypertrophy of cells.…”
Section: Ripeningmentioning
confidence: 92%
“…The relative ratio of collagen and connective tissue to smooth muscle also varies along the length of the cervix-greater in the distal region than the cervix area closer to the myometrium. In mice 4 days before birth (day 15 of a typical 19 day pregnancy), no differences in morphological or cross-linked structural characteristics were found in analysis of the ectocervix, endocervix, or transition zone (34). However, such a subregional analysis has yet to be done during the period leading up to birth at term in any species.…”
Section: Cervix Anatomy and Function For Pregnancy In Mammals At The mentioning
confidence: 99%
“…Among the myeloid cells, macrophage recruitment, traffic, activity, and polarization in both the proinflammatory (M1) and anti-inflammatory (M2) phenotypes are involved in a wide range of gestational processes such as implantation, prevention of the rejection of the fetus, the initiation of labor, and postpartum reproductive tract remodeling [5, 28, 31–36]. Moreover, the depletion of macrophages may interfere with the ripening process and account for delayed parturition [37] and disturbing the physiological system of senescent cell clearance in the postpartum uterus [32], which may be involved in successful postpartum uterine recovery to prepare for the next pregnancy.…”
Section: Introductionmentioning
confidence: 99%